Toward a general physiologically-based pharmacokinetic model for intravenously injected nanoparticles - Carlander U (Dove Medical Press, 2016)
Ulrika Carlander,1 Dingsheng Li,2 Olivier Jolliet,2 Claude Emond,3,4 Gunnar Johanson1 1Institute of Environmental Medicine, Karolinska Institutet, Stockholm, Sweden; 2Department of Environmental Health Sciences, School of Public Health, University of Michigan, Ann Arbor, MI, USA; 3BioSimulation Consulting Inc., Newark, DE, USA; 4Department of Environmental and Occupational Health, School of Public Health, University of Montreal, QC, Canada Abstract: To assess the potential toxicity of nanoparticles (NPs), information concerning their uptake and disposition (biokinetics) is essential. Experience with industrial chemicals and pharmaceutical drugs reveals that biokinetics can be described and predicted accurately by physiologically-based pharmacokinetic (PBPK) modeling. The nano PBPK models developed to date all concern a single type of NP. Our aim here was to extend a recent model for pegylated polyacrylamide NP in order to develop a more general PBPK model for nondegradable NPs injected intravenously into rats. The same model and physiological parameters were applied to pegylated polyacrylamide, uncoated polyacrylamide, gold, and titanium dioxide NPs, whereas NP-specific parameters were chosen on the basis of the best fit to the experimental time-courses of NP accumulation in various tissues. Our model describes the biokinetic behavior of all four types of NPs adequately, despite extensive differences in this behavior as well as in their physicochemical properties. In addition, this simulation demonstrated that the dose exerts a profound impact on the biokinetics, since saturation of the phagocytic cells at higher doses becomes a major limiting step. The fitted model parameters that were most dependent on NP type included the blood:tissue coefficients of permeability and the rate constant for phagocytic uptake. Since only four types of NPs with several differences in characteristics (dose, size, charge, shape, and surface properties) were used, the relationship between these characteristics and the NP-dependent model parameters could not be elucidated and more experimental data are required in this context. In this connection, intravenous biodistribution studies with associated PBPK analyses would provide the most insight. Keywords: nondegradable, PBPK, intravenous administration, phagocytosis, rats, nanorods, gold, titanium dioxide, polyacrylamide, polyethylene glycol coating